The Effects of Traditional Energy Consumption and Poverty on the Health of Rural Dwellers in Nigeria - Akintunde, Temitope Sade; Akanbi, Bosede; Adagunodo, Mathew; Akinrinde, Olawale Olufemi (EuroEconomica, 2024)
This study examines the effects of traditional energy consumption and poverty on the health status of rural dwellers in Nigeria. In an attempt to critically examine the effect of the consumption of traditional energy and poverty on the health status of rural dwellers in Nigeria, this study employs a primary survey and collects data from 1044 respondents in three (3) senatorial districts in Osun State, Nigeria. Initial findings reveal that the socio-economic conditions of households in rural areas in Osun state are significant in explaining traditional energy consumption. Additional findings further reveals that income as a proxy for poverty and energy consumption for cooking and lighting is significant in explaining the health status of rural dwellers in Nigeria. This study recommends that government should endeavour to make clean and modern energy technologies available to rural households in Osun and Nigeria in general as a practical step to addressing the poverty level and health challenges of rural dwellers. This invariably implies that government should also prioritize alleviating the people from their poor economic conditions with a view to enabling them afford clean and modern energy technologies for their energy needs.